Penyelesaian Sengketa Pegawai Pemerintah dengan Perjanjian Kerja melalui Upaya Administratif - Satya Suryo Harjanto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The dispute of government employee already changed since Law Number 5/2014 about state civil apparatur take effecty, especially related to the expansion of the legal subject of employment which includes Civil Servants and Government with Work Agreements as well as dispute resolution through administrative efforts. The problem that will be discussed is how to resolve a dispute of government employee regarding the submission of administrave effort by PPPK to a decision. This research is a normative legal research with explorative typology. The data analysis is done by qualitative analysis method, while the research tool is literature reveiw The results of the study show that in terms of legal protection there is still a disparity in disciplinary arrangements for Government Employees with Work Agreements regulated by each institution based on the characteristics of the institution so that it creates legal uncertainty if there is the dispute settlement of the termination of goverment with work agreement to Advisory Board of State Civil Apparatur (BPASN).Keywords: The dispute of government employee; Administrative Efforts; BPASN AbstrakPenyelesaian sengketa pegawai mengalami perubahan sejak berlakunya Undang-Undang Nomor 5 Tahun 2014 Aparatur Sipil Negara khususnya berkaitan dengan perluasan subyek hukum kepegawaian meliputi Pegawai Negeri Sipil dan Pegawai Pemerintah dengan Perjanjian Kerja serta penyelesaian sengketa melalui upaya administratif berupa keberatan dan banding administratif. Permasalahan yang akan dibahas adalah bagaimana penyelesaian sengeketa pengajuan upaya administratif oleh PPPK terhadap suatu keputusan. Penelitian ini merupakan penelitian yuridis normatif dengan tipologi eksploratif. Analisis data dilakukan dengan metode kualitatif dengan studi dokumen sebagai alat pengumpulan data. Hasil penelitian menunjukkan dalam hal perlindungan hukum masih terdapat disparitas pengaturan disiplin bagi Pegawai Pemerintah dengan Perjanjian Kerja yang diatur oleh masing-masing instansi berdasarkan karakteristik instansi sehingga hal tersebut menimbulkan ketidakpastian hukum apabila terjadi penyelesaian sengketa pemutusan hubungan perjanjian kerja kepada Badan Pertimbangan Aparatur Sipil Negara (BPASN)Kata Kunci: Sengketa Pegawai; Upaya Administratif; BPASN